Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2967/jnumed.114.149997
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Zero-Echo-Time MR Imaging for the Segmentation of the Skull

Abstract: MR-based attenuation correction is instrumental for integrated PET/ MR imaging. It is generally achieved by segmenting MR images into a set of tissue classes with known attenuation properties (e.g., air, lung, bone, fat, soft tissue). Bone identification with MR imaging is, however, quite challenging, because of the low proton density and fast decay time of bone tissue. The clinical evaluation of a novel, recently published method for zero-echo-time (ZTE)-based MR bone depiction and segmentation in the head is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 26 publications
3
110
1
Order By: Relevance
“…In whole-body imaging, almost all proposed methods, except joint attenuation-activity reconstruction techniques, rely on prior knowledge present in atlas images to predict bone from MRI. Moreover, owing to long acquisition time, application of ultra-short echo time (UTE) ( Keereman et al, 2010 ) or zero time echo (ZTE) ( Delso et al, 2015 ) sequences are still limited to brain imaging (single bed position). Atlas-guided segmentation has been successfully applied in various image segmentation tasks using different imaging modalities, particularly for cases with very low contrast to the surrounding tissues ( Lorenzo-Valdés et al, 2004 ).…”
Section: E-mail Address: Habibzaidi@hcugech (H Zaidi)mentioning
confidence: 99%
“…In whole-body imaging, almost all proposed methods, except joint attenuation-activity reconstruction techniques, rely on prior knowledge present in atlas images to predict bone from MRI. Moreover, owing to long acquisition time, application of ultra-short echo time (UTE) ( Keereman et al, 2010 ) or zero time echo (ZTE) ( Delso et al, 2015 ) sequences are still limited to brain imaging (single bed position). Atlas-guided segmentation has been successfully applied in various image segmentation tasks using different imaging modalities, particularly for cases with very low contrast to the surrounding tissues ( Lorenzo-Valdés et al, 2004 ).…”
Section: E-mail Address: Habibzaidi@hcugech (H Zaidi)mentioning
confidence: 99%
“…In addition, the mMR has a clinical dual ultrashort echo (UTE)-based segmentation method (8) and a prototype modelbased method (7). In turn, the SIGNA has a clinical atlas-based method and a prototype zero-echo-time (ZTE)-based segmentation method (5,16,17). The clinical atlas-AC on SIGNA is comparatively accurate in supratentorial regions, whereas not accurate enough in the infratentorial regions (5).…”
mentioning
confidence: 99%
“…Initial UTE-based AC studies have reported quantification errors of less than 5% (Aasheim et al, 2015); however, the inhomogeneous and imprecise classification of bones, particularly in the presence of diamagnetic susceptibility effects at air/bone or air/soft-tissue interfaces (Delso et al, 2014) can give rise to errors in the range 4%-17% in different regions of the brain (Dickson et al, 2014). Recently, Delso et al (2015) demonstrated that ZTE-based bone segmentation outperforms its UTE-based counterpart with reduced segmentation errors. However, these two MRI sequences are time consuming (between 3 and 6 min for low and high resolution U/ZTE acquisitions (Delso et al, 2015)), which currently limits their adoption in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Delso et al (2015) demonstrated that ZTE-based bone segmentation outperforms its UTE-based counterpart with reduced segmentation errors. However, these two MRI sequences are time consuming (between 3 and 6 min for low and high resolution U/ZTE acquisitions (Delso et al, 2015)), which currently limits their adoption in clinical practice. The assignment of constant LACs to each tissue class is another source of error in segmentation-based AC techniques, since inter/intrapatient variability of attenuation coefficients is not accounted for.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation